2023
DOI: 10.3389/fsurg.2023.916694
|View full text |Cite
|
Sign up to set email alerts
|

Subscapularis tendon tear classification and diagnosis: A systemic review and meta-analysis

Abstract: BackgroundIn the current study, we performed a systematic review and meta-analysis regarding the comparison of accuracy, sensitivity, and specificity of the techniques in diagnosing SSC tendon tears. Also, we performed a systematic review of the classification of SSC tendon tears.MethodsEnglish language, peer-reviewed journal publications from the first date available to March 2022 were extracted by searching PubMed and Web of Science databases. A forest plot was used to graphically show the results of pooled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
0
0
Order By: Relevance
“…Some of these classifications are diagnostic in physical examination, some in ultrasonography, and some in CT arthrography. Yoo and Rhee, Fox and Romeo's, Martetschlager, Lyon, Toussaint, Dierckman classifications are the classifications used in the repair of subscapular tendon tears (10). According to a survey that was conducted among elbow and shoulder surgeons in America in 2023, it was reported that the Lafosse Classification is more appropriate for the most appropriate diagnosis and treatment (11).…”
Section: Subscapularis Tears and Classificationmentioning
confidence: 99%
“…Some of these classifications are diagnostic in physical examination, some in ultrasonography, and some in CT arthrography. Yoo and Rhee, Fox and Romeo's, Martetschlager, Lyon, Toussaint, Dierckman classifications are the classifications used in the repair of subscapular tendon tears (10). According to a survey that was conducted among elbow and shoulder surgeons in America in 2023, it was reported that the Lafosse Classification is more appropriate for the most appropriate diagnosis and treatment (11).…”
Section: Subscapularis Tears and Classificationmentioning
confidence: 99%
“…Subscapularis tendon is the strongest and largest tendon of the rotator cuff, which plays an essential role in the motion and stability of the shoulder. [ 1 ] In general, subscapularis tendon tears as non-traumatic injuries are associated with subcoracoid impingement and intrinsic degeneration. Based on the subcoracoid impingement theory, the pathological mechanism is a structural narrowing in the subcoracoid space.…”
Section: Introductionmentioning
confidence: 99%